The Complete Chloroplast Genome Sequence of Callisia fragrans (Lindl.) Woodson (Commelinaceae) - Khang Vo‐Tan; Van Truong Thi Bich; Men Tran Thanh; Tai Tran Tien; Hoang Dang Khoa Do; Ngoc‐Van Thi Nguyen (Ecology and Evolution)
ABSTRACT Callisia fragrans (Lindl.) Woodson (Commelinaceae) is an invasive species in Vietnam but exhibits ornamental and potential medicinal values. However, the genomic data of C. fragrans have not been discovered. In this study, we employed the Illumina sequencing platform to complete the chloroplast genome of C. fragrans, which was 163,887 bp in length. This quadripartite genome consisted of a large single copy region of 90,751 bp, a small single copy region of 18,684 bp, and two inverted repeat regions of 27,226 bp each. Additionally, there were 79 protein‐coding genes, 30 transfer RNA genes, and four ribosomal RNA genes in the chloroplast genome of C. fragrans. Comparative genomic analysis revealed a conserved pattern of genome structure and gene content among Callisia species. However, in contrast to the pseudogenization of accD and rpoA in C. repens and C. insignis, these genes were intact in C. fragrans. Comparative genomic analysis revealed seven variable regions in the chloroplast genomes of three Callisia species, including rps16‐trnQ_UUG, psbI‐trnG_UCC, rpoB‐psbM, trnP_UGG‐rpl33, ndhF‐trnL_UAG, rps15‐ycf1, and ycf1. Phylogenetic analysis indicated the monophyly of Callisia species and a close relationship between C. fragrans and C. repens. This study provides initial data of the chloroplast genome for further genomic studies examining genetic populations, phylogeny, and molecular markers of C. fragrans and related species in Commelinaceae.